Патология прикрепления пуповины в экстрахориальной плаценте как причина острой гипоксии плода - Мельников, Андрей Павлович; Аксёнов, Анатолий Николаевич; Аксенова, Анастасия Александровна; Дзюба, Галина Сергеевна; Улятовская, Виктория Ивановна (Медицина: теория и практика, 2020)